Utilization of Artificial Intelligence in Monitoring and Mitigating National Security Threats - Wiranata, Angga Junior (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2024)
Implementing Artificial Intelligence (AI) in the context of national security has become a critically important topic in addressing increasingly complex modern threats. This article examines various AI applications in monitoring and mitigating national security threats, such as managing critical infrastructure, risk assessment, and adaptive responses to crises. By adopting the socio-technical systems theory approach, this approach recognizes the complexity of interactions between AI technology, human decisions, and operational environments that impact national security. Recommendations include increased investment in advanced AI infrastructure and more profound training for AI and the national security workforce. It is expected that mature AI implementation can significantly impact maintaining stability and national security in this dynamic digital era.